PETA PENGEMBANGAN SAPI POTONG DI KABUPATEN BANJARNEGARA - Abdul Aziz Ahmad; Moch. Sugiharto (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2014)
The main issue of the last years in Indonesian livestock production systems is declining beef cattle population. The problem always recurs. Another problems that emerge are restrictively of animal husbandry land, climate uncertainty, the lack of livestock technological adoption, and also insignificant economic of scale in livestock production. Therefore, en effort to develop beef cattle is optimize potency of endowment capabilities. Banjarnegara District is a region that could be identified to have the potencies. For the first stage is a requirement to make potencies mapping analysis to strive for developing of beef cattle. The mapping is based on expert judgment method. It is grouping of potencies areas layers is determined by some indicators which is classified into natural or physical resources (included into pasturage, superior grass, dried rice stalks, marginal terrain, rainfall, livestock density, and human population density), human resources (experience of cow breeding, and education of breeder), infrastructure condition and availability (livestock market, transportation, and feed livestock), and also social endowment (breeder association). The potencies mapping analyses shows that fattening or cultivation of beef cattle is majority of dairy farming of cow breeder Bajarnegara District, than dairy cattle. The suitable areas to the cultivation are in the place that there are potencial and sufficient of grass feeding. There are Subdistrict of Wanayasa, Punggelan, Kalibening, Bawang, Pandanarum, Purwanegara, Pagedongan, Banjarmangu, and Madukara.Keywords: livestock, beef cattle, mapping, Banjarnegara District